The Miska - Dalle, Luis (1971)
Miska, in Quechua, is a tender, first-time fruit. Miska is also the very first planting of corn, whose fruit will be consumed, in the form of tender corn, before it reaches maturity. The sowing of the miska is done on a small scale, for the needs of the pantry.